Editorial - Aguirre Chavez, Felipe (2021)
There are important moments and events in the life of institutions, and for us, some of these moments will be captured in the publication of another issue of our institutional journal, Educa UMCH. Although the initial response wasn't overwhelming, we are hopeful and optimistic that the five articles in issue number 14 of our Educa UMCH journal represent a significant achievement, with prospects and rewards that will continue to grow as the future unfolds.